KONSEP ‘MATI SEBELUM WAKTUNYA’ DALAM PENGKHOTBAH 7:17: SUATU TELAAH TEOLOGIS DAN EKSEGETIS - Timotius Bakti Sarono (Sekolah Tinggi Teologi Arastamar Bengkulu, 2026)
This study aims to explore the meaning of the phrase “to die before one’s time” as found in Ecclesiastes 7:17, within the framework of biblical wisdom literature. The phrase is often understood as the moral and spiritual consequences of a life marked by wickedness and foolishness. This study uses exegetical and semantic approaches to analyze Hebrew root words such as רָשָׁע (rashaʿ) for “wicked” and סָכָל (sakal) for “foolish,” as well as עֵת (ʿet) which refers to “time” or “season.” The results of the analysis show that “to die before one’s time” is not simply a biological event, but a theological expression that implies a discrepancy between God’s will and human life choices. In the Hebrew wisdom tradition, this kind of death is seen as the result of a rejection of the ethical and spiritual values ​​embedded in God’s law. This study also highlights how the doctrine of free will plays a role in determining these existential consequences. Thus, the text of Ecclesiastes 7:17 becomes an important reflection of biblical ethics and spirituality that emphasizes the interconnectedness of moral choices, wise living, and human life time.